Changes in surface velocities over four decades on the Laurichard rock glacier (French Alps). (22nd June 2022) - Thibert, Emmanuel; Bodin, Xavier
Abstract: The longest time series of surface velocities recorded on a rock glacier in the French Alps, covering more than three decades, has been recorded since 1983 on the Laurichard rock glacier (Ecrins range). The time signal of velocity changes is extracted from variance analyses separating time and space variabilities on the rock glacier surface to provide an average‐wide time signal. We show that changes in velocity from year to year are virtually uniform at all locations with homogeneous accelerations or decelerations on the scale of the rock glacier as a whole. The spatial structure of velocity was found to be nearly at steady state over 35 years. Nonlinear effects are located in low‐velocity areas such as the rock glacier margins where accelerations/decelerations tend to be proportional to the local velocity. Over the period of record, a long‐term trend in rock glacier acceleration was detected with a rate of +0.2 m/yr per decade. Two main phases of acceleration were identified from the mid‐1980s to 1999 and from 2010 to 2015. In between, those two periods were interrupted by a 10‐year period of almost steady‐state velocities with an abrupt deceleration from 2006 to 2009 of −0.35 m/yr. The process of internal increases in ice temperatures alone (and associated changes in creep rates) would seem insufficient to explain the long‐term rise of surface velocities and their annual variations. Changes in the liquid water are a possible contributing factor, due to the injection of seasonal water caused by melting snow cover or internal melt due to heat generated by enhanced ice creep and friction in the ice/debris mixture.